The Rate of Low Vision Aids Usage after Prescription at the Saba and Khazaneh Clinics in Low Vision Clients - Nasser Sadegh-Pour; Gholam Hossein Sazmand; Akbar Biglarian (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: This research was aimed to determine the rate of low vision aids uses by low vision clients in their daily living. Materials & Methods: In this descriptive study that was done at the Saba and Khazaneh clinics, 50 people from low vision clients were selected by convenient sampling during 2005 & 2006. One questionnaire was completed by therapist at the first time of optometric examination and useful low vision aid (LVA) has been prescript and given to clients. After three months (at least) they should came back to center and fill the second form. The first form was about functional vision without LVA and second too, but by using of LVA. They have been compared to fulfill the result of research. Data were analyzed by Spearman correlation coefficient, Chi - square and Wilcoxon tests. Results: Spearman correlation coefficient between use of LVAs for near with duration and frequency of study were 0/491 and 0/520 with probability values such as P=0/003 and P=0/002 that shown significant relation. There was significant difference in traffic measure and environment knowing between before and after of far LVAs using (P=0/002) and their SCC was 0/499. There was significant relation between use of low vision aid and education after prescription (P=0/011). Conclusion: However the LVAs improve vision of low vision person, but many of them don't use by different reasons.